Managing Challenges in Organic Photovoltaics: Properties and Roles of Donor/Acceptor Interfaces - Liu, Yanfeng; Wu, Yue; Geng, Yanfeng; Zhou, Erjun; Zhong, Yufei (Advanced functional materials, 2022)
Organic photovoltaics (OPVs) have demonstrated increasing potential for use in large‐area, flexible, and light‐weight applications. To date, the rapid development of nonfullerene acceptors (NFAs) and their conjugated polymeric donors have increased the efficiency of OPV by over 19%. Nevertheless, OPV is still suffering from high energy loss, which primarily derives from the donor (D)/acceptor (A) interfacial charge recombination. In particular, the voltage loss occurring at the D/A interface accounts for the current bottleneck, hampering further enhancement of the OPV efficiency. In this review, the recent discovery of D/A interfacial photophysics in NFA‐based OPVs, including the comparison with its fullerene‐based counterpart, is covered. Additionally, the factors governing interfacial energy loss, such as interfacial energetics and local morphologies, which causes the trade‐off relationship between photovoltage and photocurrent in OPV are highlighted. Accordingly, the control of D/A interfacial properties to create an “ideal” interface for charge generation in OPVs is reviewed; and emphasized that the D/A interfacial modifications can serve as a powerful tool to manage the challenges in OPVs path toward future practical applications. Donor/acceptor interfacial properties strongly influence the performance of organic photovoltaics via processes such as charge transfer, delocalization, and recombination that can set the fundamental efficiency limit of such devices. The screening of this interface can provide the tools (interfacial modification) to optimize the trade‐off in device figure of merit.